Test-Taking Strategies in Reading Comprehension Tests: Insights from Freshman and Senior High School EFL Learners - Alireza Asltaleb Maghferat; Parviz Ajideh; Shahabaddin Behtary (International Journal of Practical and Pedagogical Issues in English Education)
Test-taking strategies (TTSs) have been found to be closely related to EFL learners’ successful language acquisition. However, such strategies have received scant attention from a language testing perspective (Bachman, 1990). The current mixed-methods study aimed to investigate Iranian freshman and senior high school EFL learners’ use of TTSs in reading comprehension tests and their perceptions of TTSs. To this end, 30 freshman and 30 senior high school EFL learners were selected from a public high school in Tabriz, Iran. The participants were asked to complete a questionnaire on TTSs. Afterward, six participants (three from each grade) were randomly invited for semi-structured interviews. SPSS software (version 27) was used to analyze the quantitative data gathered from the questionnaires, while the content analysis approach was utilized to analyze the qualitative data collected from the semi-structured interviews. The results indicated that senior participants used monitoring strategy the most, while freshman participants mostly used planning strategy. It was also found that both groups of participants had positive perceptions towards learning, teaching, and using TTSs. Implications are also presented as to the need for incorporating TTSs into teaching/learning methodologies, curricula, and materials.